Effect of partial substitution of wheat flour by soybean meal in technological and sensory characteristics of cupcakes for children of school age - Paucar-Menacho, Luz (2016)
The objective of this research was evaluate the effect of the partial substitution of wheat flour by soybean meal (HS) in the technological and sensory characteristics of cupcakes, in order to develop a high-protein food for school-age students. Common wheat flour was replaced with four different percentages of HS: 5% (F1), 10% (F2), 15% (F3) and 20% (F4), these were compared with a control sample with 0% (F0) of HS. The technological characteristics evaluated were weight loss, water activity (Aw), instrumental color, bulk and texturometria samples, for 12 days. The results showed that the substitution of HS improves firmness of cupcakes and helps moisture retention, a substitution until F2 was not significantly different from F0. A test to 45 panelists with a hedonic scale for sensory evaluation was used; three sensory characteristics (color, flavor and texture) and purchase intent were evaluated. The cupcakes with HS presented significant differences in color in relation to F0; the results indicated that this ingredient could replace wheat flour F0 up to 10%, without significantly altering its sensory quality. As for the intention to purchase, F2 obtained a score of 4.20 ± 0.53 on a scale of 5 points, which does not differ significantly from F0.